2006
DOI: 10.1002/ajmg.b.30291
|View full text |Cite
|
Sign up to set email alerts
|

Association of AKT1 haplotype with the risk of schizophrenia in Iranian population

Abstract: AKT-glycogen synthase kinase 3beta (GSK3beta) signaling is a target of lithium and has been implicated in the pathogenesis of mood disorders and schizophrenia. AKT1 protein level is decreased in the peripheral lymphocytes and brains of schizophrenic patients. The SNP2/3/4 TCG haplotype of AKT1 was associated with schizophrenia in patients with Northern European origin. In the present study, we genotyped five single nucleotide polymorphisms (SNP1-5) of AKT1 gene according to the original study in Iranians compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 22 publications
(53 reference statements)
3
44
1
Order By: Relevance
“…Interestingly, haplotype 1-5 (rs1130214-rs2494732) whose 2 SNPs singly showed trends toward significance (Supplementary Table S1), is most significantly associated with TRANSMIT/PDTPHASE at broadest diagnostic category D9 (0.0002<global p<0.045; Supplementary Table S2). We saw no association with 'risk' haplotypes of Ikeda et al (13), or the tested portion of the Bajestan et al (14) risk haplotype.…”
Section: Exploratory Analysis -All 2-4 Snp Haplotypescontrasting
confidence: 64%
See 2 more Smart Citations
“…Interestingly, haplotype 1-5 (rs1130214-rs2494732) whose 2 SNPs singly showed trends toward significance (Supplementary Table S1), is most significantly associated with TRANSMIT/PDTPHASE at broadest diagnostic category D9 (0.0002<global p<0.045; Supplementary Table S2). We saw no association with 'risk' haplotypes of Ikeda et al (13), or the tested portion of the Bajestan et al (14) risk haplotype.…”
Section: Exploratory Analysis -All 2-4 Snp Haplotypescontrasting
confidence: 64%
“…Association between AKT1 and schizophrenia has been replicated in 3 independent studies: 79 Caucasian sib-pair families (12), a Japanese 507 case −437 control sample (13) and an Iranian 321 case −383 control sample (14). Schwab et al (12) found association with rs3730358 (p=0.027), but more significantly with 5'UTR SNPs, rs1130214 (p=0.011) and rs10149779 (p=0.002).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has a basic role in regulating neuronal cell size and survival (Franke, 2008) and is also a key signaling molecule downstream of the dopamine D2 (DRD2) receptor; decreased AKT1 functionality may result in exacerbated responses to DRD2 receptor stimulation (Arguello and Gogos, 2008). Decreased AKT1 levels have been observed in lymphoblasts and postmortem prefrontal cortex of patients with schizophrenia (Emamian et al, 2004;Thiselton et al, 2008), and several studies have shown evidence for genetic association with schizophrenia (Bajestan et al, 2006;Ikeda et al, 2004;Norton et al, 2007;Schwab et al, 2005;Thiselton et al, 2008), although not all studies were able to confirm this (Ide et al, 2006;Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The gene coding for AKT1 (14q32.32) has also been associated with schizophrenia (31,32,(34)(35)(36)(37). Importantly, the A allele in a synonymous SNP in AKT1 (rs1130233 − G > A) is associated with reduced AKT1 protein levels in lymphoblasts (38,39), reduced cognitive performance, inefficient prefronto-striatal activity during cognition (39), as well as with diagnosis of schizophrenia (39).…”
mentioning
confidence: 99%